Depressive State in the Emergency Department During COVID-19: A National Cross-Sectional Survey in China - Liu, Shuang; Han, Wei; Shen, Chenyu; Zhu, Changju; Wang, Qiaofang; Liang, Xianquan; He, Xiangxi; Xie, Qin; Wei, Jie; Wu, Miao; Zhao, Xiaodong; Liu, Hongsheng; et al. (Frontiers in Psychiatry, 2021)
Chinese emergency medical staff encountered significant mental stress in fighting the coronavirus disease 2019 (COVID-19) pandemic. We sought to investigate the prevalence and associated factors for depressive symptoms among this group. A cross-sectional national survey of general emergency medical staff who were on duty and participated in fighting the COVID-19 pandemic work was conducted from March 1-15, 2020. A total of 6588 emergency medical staffs from 1060 hospitals responded to the survey. Chinese emergency medical staff did experience depressive symptoms during the COVID-19 period, particularly those aged 31-45, those working in the COVID-19 isolation unit, and those living with those ≤ 16 or ≥ 70 years old. These results detail the prevalence and associations of depressive symptoms among Chinese emergency medical staff and reinforce the importance of targeted staff support during COVID-19 or future outbreaks.